2006
DOI: 10.1016/j.wear.2005.02.121
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between wear and dissipated energy in sliding systems

Abstract: Wear is the progressive loss of material from the operating surface of a body occurring as a result of relative motion at the surface, while friction is the main means of controlling the input of energy in a system. The tribosystem approach proposes analysing the contact on both the material and the energetic planes, but the relationships between the different planes are not well established. In this paper, the basis of the energetic approach is discussed and the application of the model to experimental studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(122 citation statements)
references
References 13 publications
8
114
0
Order By: Relevance
“…Huq and Celis [42] conclude that the more complexity in wear process arises when one considers the interactions not only between the contacting surfaces but also with the surroundings. A similar study on the energetic approach to wear is reported by Ramalho and Miranda [43]. Interestingly, they show that the energy dissipated in the contact is linearly correlated with the wear volume during sliding wear and that the results can be used to quantify the wear coefficient in Archard's equation.…”
Section: Sliding Contactsupporting
confidence: 69%
See 1 more Smart Citation
“…Huq and Celis [42] conclude that the more complexity in wear process arises when one considers the interactions not only between the contacting surfaces but also with the surroundings. A similar study on the energetic approach to wear is reported by Ramalho and Miranda [43]. Interestingly, they show that the energy dissipated in the contact is linearly correlated with the wear volume during sliding wear and that the results can be used to quantify the wear coefficient in Archard's equation.…”
Section: Sliding Contactsupporting
confidence: 69%
“…Therefore, the volume of wear is directly proportional to the energy dissipated by friction. Figure 5 shows several experimental results reported by Ramalho and Miranda [43] for wear volume versus dissipated energy for different materials. Indeed, experimental results of Ramalho and Miranda [43] reveal that the rate of change in the wear volume is linearly related to the dissipated energy and that the slope of the line represents an estimation of the wear coefficient,…”
Section: Sliding Contactmentioning
confidence: 99%
“…Once the normal and tangential contact conditions have been calculated with the semi-analytical solver, the wear energy approach [2,[22][23][24] is used to compute fretting wear. In this approach, the total wear volume obtained after N cycles is assumed to be proportional to the accumulated dissipated energy:…”
Section: Wear Computationmentioning
confidence: 99%
“…This would demonstrate a dependence of friction dissipation in sliding solids through three processes: rise in temperature; wear particle generation; and the entropy changes associated with material transformation in the interface. 7,25 In this work, we determine a correlation between damage entropy and the resistor's resistance evolution, which may help for resistor damage diagnosis and prognosis. The form of _ S i will be discussed later in light of the experimental results.…”
Section: Theoretical Approachmentioning
confidence: 99%